Relationships Between the Amplitudes of the Components of Visual Evoked Potentials in Men and Women with Different Cognitive Activity Characteristics - Nadezhda I. Belousova; Pavel V. Tkachenko; Elena V. Petrova (Northern (Arctic) Federal University, 2024)
Human life is invariably associated with continuous cognitive processes that depend on the ways and characteristics of perception, processing and reproduction of information, as well as on the control strategy determining the level of cognitive activity. Previous research of the authors of this paper revealed pronounced sex-related differences in psychophysiological processes. These differences are manifested in the perception of information, realization of voluntary motor activity, and formation of a typological complex of resistance to monotonous activity. A number of studies have shown the importance of detection, dissemination and duplication of sensory information in the central structures of the central nervous system for effective implementation of voluntary motor activity. It is obvious that the specifics of the perceptual activity of visual cues and voluntary activity indicators will determine the result and efficiency of the the body's function. The purpose of this paper was to study the intrasystem relationships of the activity characteristics of the central elements of the visual sensory system by recording visual evoked potentials following presentation of a chess pattern, taking into account the subjects' sex and cognitive activity features, i.e. field dependence or independence. Materials and methods. The experiment involved relatively healthy students aged 18-20 years (41 men and 54 women), who signed informed consent. We analysed the total multilateral correlations between the amplitudes of visual evoked potentials following presentation of a chess pattern in subjects at different poles of the field dependence/independence cognitive style. Results. We found recti- and curvilinear intrasystem relationships of the activity characteristics of the elements of the visual sensory system which indicate that being at a certain pole of the field dependence/independence cognitive style affects one's perception mechanisms. Men demonstrate pronounced manifestations of attunement and co-attunement of this activity in the form of curvilinear relationships. In women, the systems are more rigidly, strongly determined in their relationship structure. These facts indicate sex-related and style differences in visual perception strategies in men and women at different poles of the cognitive style.